2012
DOI: 10.1111/ele.12032
|View full text |Cite
|
Sign up to set email alerts
|

Sticky plant traps insects to enhance indirect defence

Abstract: Plant-provided foods for predatory arthropods such as extrafloral nectar and protein bodies provide indirect plant defence by attracting natural enemies of herbivores, enhancing top-down control. Recently, ecologists have also recognised the importance of carrion as a food source for predators. Sticky plants are widespread and often entrap and kill small insects, which we hypothesised would increase predator densities and potentially affect indirect defence. We manipulated the abundance of this entrapped insec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
86
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 24 publications
4
86
0
Order By: Relevance
“…Examples include acacias, which provide shelter and food bodies to ants, which deter herbivory (Madden and Young 2002) and Viburnum species, which provide domatia and extrafloral nectar to predatory and mycophagous mites (Weber et al 2012). Recent evidence suggests that arthropod carrion adhered to plant surfaces also provisions mutualistic predators (Ellis and Midgley 1996, Anderson 2005, Sugiura and Yamazaki 2006, Romero et al 2008, Krimmel and Pearse 2013Appendix A). Carrion provisioning usually begins with an adhesive surface, composed of glandular or hooked trichomes, which entraps insects (in addition to other functions of the trichomes).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Examples include acacias, which provide shelter and food bodies to ants, which deter herbivory (Madden and Young 2002) and Viburnum species, which provide domatia and extrafloral nectar to predatory and mycophagous mites (Weber et al 2012). Recent evidence suggests that arthropod carrion adhered to plant surfaces also provisions mutualistic predators (Ellis and Midgley 1996, Anderson 2005, Sugiura and Yamazaki 2006, Romero et al 2008, Krimmel and Pearse 2013Appendix A). Carrion provisioning usually begins with an adhesive surface, composed of glandular or hooked trichomes, which entraps insects (in addition to other functions of the trichomes).…”
Section: Introductionmentioning
confidence: 99%
“…Thomas (1988) found that eliminating the sticky trap significantly reduced the abundance of the most common predator on Cirsium discolor (Asteraceae), but not on Penstemon digitalis (Plantaginaceae). In the most extensive test of this defense, Krimmel and Pearse (2013) demonstrated each of these links experimentally by adding insect carrion to Madia elegans (Asteraceae), and Romero et al (2008) convincingly demonstrated predator-mediated herbivore reduction on a sticky plant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Predator attraction to leaves was found to increase plant fitness in many cases, i.e., by producing extrafloral nectaries that feed bodyguards, 23 by emitting volatiles [24][25][26] and by sticking small insects to leaves by sticky trichomes. 27 The visual aspect of plant movement as a way of communication with (and deception of) animals has already been studied…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…9 The study of insects has so far mainly been dependent on manual counting and analysis using, e.g., light traps, flight intercepts traps, pitfall traps, water pan trap, beating trays, and sweep nets. [10][11][12][13][14][15] Such methods have been used for many years, and have made significant contributions to the field of ecological entomology. However, it remains challenging to investigate fast interaction mechanisms or a vast number of insects using the conventional techniques in situ.…”
Section: Introductionmentioning
confidence: 99%